Aplikasi Pembelajaran Interaktif Hewan Endemik Nusantara Berbasis Android - Daniel Timothy Imannuel Silalahi; Intan Meutia Sari; Tiya Noviyanti (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
In today's digital era, advances in technology and science are growing very rapidly. Of course, advances in technology and science affect various things. One of them android-based gadgets is utilization to make it easier to find information or knowledge that can be easily accessed. This research aims to design and create an application for the introduction of endemic animals in Indonesia. Endemic animals are species that only exist in certain places and are not found in other places, such as islands, countries, or other geographic areas. Android is an operating system that has an open source nature that allows it to make it easier to recognize and access information about Endemic Animals in Indonesia. The research method for designing and making applications uses the Software Development Life Cycle (SDLC) method. The method begins with planning, analysis, design, implementation and testing. The final result of this research is an application for the introduction of endemic animals in Indonesia based on android. This application was successfully made with appropriate material and quiz features. Function testing on each feature is done with the black box method to ensure the material runs well to display images and material and the function on the quiz feature can function properly. Tests were also conducted with 3 android devices with different versions, namely versions 10, 12, and 13.